Factors Affecting Firm Value with Capital Structure As A Moderating Variable - Kusumawati, Annisa; Primasari, Niken Savitri (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
This study aims to examine the factors that affect firm value with capital structure as a moderating variable on the compass 100 index. The sample selection used in this study was 37 companies in the compass 100 index using purposive sampling. This study uses the WarpPLS 7.0 application to analyze the data. The results of this study indicate that ROA has a negative effect on firm value, NPM has no effect on firm value, firm size has a negative effect on firm value, and investment decisions have no effect on firm value. Capital structure is able to moderate the effect of ROA on firm value, capital structure is able to moderate the effect of NPM on firm value, capital structure is not able to moderate the effect of firm size on firm value, and capital structure is not able to moderate the effect of investment decisions on firm value.